The Evian Conference from a Different Perspective?: The Estonian-German-Japanese Joint Intelligence Operations against the Soviet Union in the Summer-Autumn of 1938. - Shingo Masunaga (Vilnius university, 2022)
The Évian Conference of July 1938 was a historic event in the history of European Jews. The delegates from 32 countries all around the world failed to reach an agreement regarding the acceptance of Jewish refugees from Germany and former Austria. Ultimately, the failed conference led to the genocide of the Jewish refugees in the 1940s. Meanwhile, at the time of the conference, the German military intelligence service (Abwehr) under the command of Admiral Wilhelm Canaris has been actively organizing intelligence operations against the Soviet Union in Estonia together with the local Estonian and Japanese intelligence services. Contrary to the persecution of the Jews in the Third Reich, the Germans employed the émigrés for intelligence operations against the Soviet Union. The author of the article tried to sum up the trilateral intelligence activities of Estonia, Germany and Japan, which could be helpful in understanding or analyzing the Évian Conference from a different perspective.
Conventions, quotas, refugees: European jews in 1938–1945